BEBAN ADMINISTRATIF DAN KURANGNYA PELATIHAN GURU DALAM IMPLEMENTASI KURIKULUM MERDEKA DI SDN PANGERAN 1 - Novi Handayani; Putri Normeiliani; Aslamiah; Diani Ayu Pratiwi; Shintiya Andini; Zaliha (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The implementation of Merdeka Curriculum at SDN Pangeran 1 faces various complex challenges. One of the main problems is the high administrative burden and limited training for teachers. Although the Merdeka Curriculum is designed to provide flexibility for teachers in developing a learning process that suits the characteristics and needs of s tudents, in practice, many teachers feel even greater pressure. Administrative demands such as preparing teaching modules, filling in learner progress reports and making other teaching tools drain a lot of their time and energy. As a result, focus and creativity in the learning process in the classroom is often reduced. In addition, the lack of intensive training and assistance in understanding and implementing Merdeka Curriculum makes some teachers feel less confident and have difficulty innovating. This study aims to explore school policies in implementing the Merdeka Curriculum as well as the strategies used to overcome the obstacles faced by teachers. The approach used in this research is qualitative, which is conducted through in-depth interviews with principals and teachers, direct observation in the school environment, and analysis of relevant policy and administrative documents. The results showed a gap between the expectations of the curriculum and the reality in the field. Therefore, collaborative efforts between the school and the education office are needed to simplify the administrative burden, provide clear and practical implementation guidelines, and organize continuous training so that teachers can implement Merdeka Curriculum effectively and meaningfully.